Dampak Negatif Cyberbullying dan Upaya Pencegahannya - Dahliana Purba, Nursenta; Octavia Turnip, Sontiarma (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2024)
The development of technology has both positive and negative impacts on human life. One of the negative impacts is the prevalence of cyberbullying. Cyberbullying can affect anyone and involves various actions such as defamation, insults, intimidation, and discrimination. Its negative effects can harm both individuals and society at large. This study aims to understand the negative impacts of cyberbullying and efforts to prevent it. The research method used is qualitative with a literature review, involving the collection of data from books, journals, and previous studies. The data is analyzed critically and in-depth to support the propositions and ideas in this research. The results of the study indicate that cyberbullying has significant negative effects on individuals and society. These negative effects can include psychological trauma, reputation damage, and even death. Efforts to prevent cyberbullying need to be carried out comprehensively, starting from the family environment, church, and cooperation with the government.